The Rehabilitation of Al-Rabiaya Mosque in Old City of Mosul (Journal of Planner and Development, 2012)
This paper tackles the problematic of the deterioration and dilapidation of numerous historical and traditional mosque buildings (including Rabayia Mosque 1762A.D.-1180A.H.) in the old city of Mosul. These buildings are currently threaten by distortion, loss and dilapidation. Some of their features have been erased particularly in the recent decades due to natural and human factors besides improper conservation work. The paper drives at fulfilling the conservation work by way of practical experiment (carried out by the researcher) on Rabayia mosque all within a complementary project encompassing architectural and modern facilities which conduced to the discovery of various architectural treatment and solutions. The effect was to prevent any further distortions and erosions of the old mosque building. The techniques, engineering and scientific methods used achieve sustainability, duo ability and innovation with aesthetic, historical and sensational repercussions on society.